Working Time, Knowledge Work and Post-Industrial Society - O'Carroll, A. author. aut Link
VIII, 183 p.
Keywords: We are living in the age of imagination and communication. This book, about the new ways time is experienced and organised in post-industrial workplaces, argues that the key feature of working time within knowledge, and other workplaces, is unpredictability, creating a culture that seeks to insert acceptance of unpredictability as a new 'standard'.